Clinical Case of the Use of Mr Tractography in Patients with Optochiasmal Arachnoiditis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Optochiasmal arachnoiditis (OCA) is one of the most severe diseases that leads to blindness or severe disability in young people. Optochiasmal arachnoiditis is a clinical syndrome of a chronic productive inflammatory process of the brain and its membranes with predominantly damage to the chiasm area and optic nerves. The disease is characterized by a variety of clinical manifestations and severe visual impairment.